Clinical and laboratory aspects of early diagnostics meningitis and meningoencephalitis induced by tick-borne encephalitis - N. P. Tolokonskaya; Yu. V. Kazakova; E. A. Spiridonova; T. G. Burmistrova; V. V. Provorova (Бюллетень сибирской медицины, 2008)
Clinical displays of the early period of meningitis and meningoencephalitis induced by tick-borne encephalitis have significant similarity and can not serve as reliable criteria of weight, the forecast and differential to therapy. Mixed somatic pathology of degenerative nature, which was revealed in the study of the majority of patients with tick-borne encephalitis, more often including the initial central nervous system affliction under conditions of negative changes of organism reactivity, is regarded as one of the main reasons of infection conversion into disease. The virus becomes an aggression factor at such joint biological causes, changing endobiocenosis, which is of great importance for substantiation of curing therapy.